Novas modalidades de sitcom: uma análise da comédia na era da realidade espetacularizada - Ceretta, Fernanda Manzo (2014)
This research intends to analyze north-American serial comedies that parody the documentary decoupage. The Office, Parks and Recreation and Modern Family, productions in the corpus of this research, are representatives of a recent trend in the United States television programming. This trend, which was intensified since the mid 2000s, features the fictional comic text in documentary language, building a particular relationship with the discourse of factuality. This format breaks with an established practice of the traditional sitcom. According to researchers, the way in which sitcoms were presented was stagnant, with the same characteristics since I Love Lucy, televised in the 1950s. This research seeks to investigate the peculiarities of the construction of comedy in the text and decoupage of the products mentioned, as well as the possible relationship between the current popularity of this format and the television context: a programming full of reality shows and the massive amateur audio-visual production on the internet. The hypothesis presented is that there is a new viewer's relationship with the discourse of factuality. Methodologically, the research will be bibliographic and documentary, involving interviews with TV authors in specialized publications and bibliography. The fundamental theoretical and methodological basis of the research is in the works Jon Dovey and Mark Andrejevic on reality TV and Brett Mills and Anthony Savorelli on sitcom